PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN ASET SEBAGAI VARIABEL PEMODERASI - Kadek Ayu Laksmita; Ni Komang Sumadi; I Putu Fery Karyada (Hita Akuntansi dan Keuangan, 2020)
The purpose of this research to find influence of liquidity and leverage on the financial performance with management assets as moderating variabel of trade and non financial service sector in Indonesia Stock Exchange in 2016 to 2018. Data analysis technique used is multiple linear regression analysis and sample using purposive sampling technique and obtained 78 companies in each year. The results of showed liquidity, leverage, and management assets simultaneously affect on the financial performance. Partially liquidity had a positive effect on financial performance. As for leverage variable had a significant negative effect on financial performance. In this research also shows the role of management assets is not able to moderate the influence of liquidity on the financial performance. Management assets also not be able to moderate the influence of leverage on the financial performance.